Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T16:14:45+01:00
A) 2x(x+2y)-x(2x+y) =2x²+4xy-2x²-xy = 3xy
b) -x(z-y)-z(-x+y) =-xz+xy+xz-zy = xy-zy
c) 4(x+y)-2(x-y)-3x(1+y) =4x+4y-2x+2y-3x-3xy=-x+6y-3xy
d) -5x(2-y)-y(5x+1)+10x(-y+1) = -10x+5xy-5xy-y-10xy+10x=-y-10xy
  • Grel
  • Początkujący
2009-12-01T16:15:46+01:00
2x(x+2y)-x(2x+y)=2x²+4xy-2x²-xy=3xy
-x(z-y)-z(-x+y)=-xz+xy+xz-zy=xy-xz
4(x+y)-2(x-y)-3x(1+y) = - x + 6y - 3xy
-5x(2-y)-y(5x+1)+10x(-y+1) = -y -10 xy
2009-12-01T16:16:51+01:00
A)3xy
b) xy - zy
c)-x + 6y - 3xy
d)-y -10 xy